Pengembangan Software Pembelajaran Interaktif Geometri Sltp Studi Kasus Segitiga Dan Lingkaran - Lina Sulistyani; palgunadi .; dahlan susilo (Universitas Sahid Surakarta, 2009)
Traditional geometry learning method needs a condiserable long enough time. This problem can cerise an effort to an interactive geometry learning develop. To develop the application software it need an alogaritm and specification on the basic geometry shape, especially on triangle and circle. of this research is to develop a RAISE Specification on triangle and circle as well as to develop an interactive GUI software with Java program. The main steps on the rescarh conducted are to develop RAISE Soecification on point, triangle and circle in 2D geometry, to develop a software GUI implementation with Java programming in Netbeans 6.0 the triangle is an extend of point to test the correctness of specification and alogaritm, it is used a Boundary Value Test. If can be concluded that the specification and alogaritm are already developed and tested. Those specifications are also correct to be implemented on cases on triangle and circle it is also develop a GUI interactive software on Java programming